2013
DOI: 10.1016/j.chom.2013.10.010
|View full text |Cite
|
Sign up to set email alerts
|

The Intracellular Cargo Receptor ERGIC-53 Is Required for the Production of Infectious Arenavirus, Coronavirus, and Filovirus Particles

Abstract: SUMMARY Arenaviruses and hantaviruses cause severe and often fatal diseases in humans. Little is known regarding host proteins required for their propagation. We identified human proteins that interact with the glycoproteins (GPs) of a prototypic arenavirus and hantavirus and show that the lectin ERGIC-53 - a cargo receptor required for cellular glycoprotein trafficking within the early exocytic pathway - associates with arenavirus, hantavirus, coronavirus, orthomyxovirus, and filovirus GPs. ERGIC-53 binds to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
70
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 38 publications
1
70
0
3
Order By: Relevance
“…The GPC precursor is trafficked from the endoplasmic reticulum to the Golgi, where it is heavily N-glycosylated and processed by cellular proteases [signal peptidase (SPase) SKI1/SP1] into its mature form, which comprises noncovalently linked GP1, GP2, and SSP (18). GPC must also interact with ERGIC-53 in the exocytic pathway in order to form infectious virions (19). …”
mentioning
confidence: 99%
“…The GPC precursor is trafficked from the endoplasmic reticulum to the Golgi, where it is heavily N-glycosylated and processed by cellular proteases [signal peptidase (SPase) SKI1/SP1] into its mature form, which comprises noncovalently linked GP1, GP2, and SSP (18). GPC must also interact with ERGIC-53 in the exocytic pathway in order to form infectious virions (19). …”
mentioning
confidence: 99%
“…There is growing evidence that ERGIC-53 is closely related with virus infection. ERGIC-53 is required for the production of infectious arenavirus, coronavirus, and filovirus particles [11]. In the present study, a LTL (named PcL-lectin) was identified from red swamp crayfish, Procambarus clarkii.…”
Section: Introductionmentioning
confidence: 80%
“…In this issue, Klaus et al (2013) identify the cargo receptor endoplasmic reticulum (ER)-Golgi intermediate compartment 53 kDa protein (ERGIC-53) as a binding partner for viral GPs and a crucial cellular factor required for infectious virus production. In this issue, Klaus et al (2013) identify the cargo receptor endoplasmic reticulum (ER)-Golgi intermediate compartment 53 kDa protein (ERGIC-53) as a binding partner for viral GPs and a crucial cellular factor required for infectious virus production.…”
mentioning
confidence: 99%
“…In this issue of Cell Host & Microbe, Klaus et al (2013) sought to close this gap by performing a broad proteomic screen to identify cellular proteins that interact with viral envelope GPs. Enveloped viruses hijack the host cell's secretory pathway for GP biosynthesis.…”
mentioning
confidence: 99%